Research of the features of the human organism and limbs in the development of large-sized anatomical footwear for household and special purposes - Липський, Т. М.; Бабич, А. І.; Липський, А. С. (Fashion Industry, 2026)
Purpose. Introduction of modern innovations, as well as technologies for manufacturing anatomical footwear of large sizes for individual orders, which contributes to the creation of high-quality, comfortable, modern and exclusive products that combine design, manufacturability and comfort. Methodology. The work used methods of theoretical and analytical research of anatomical, physiological and anthropometric features of the human body and limbs, bibliometric analysis of scientific sources on the topic of the study, experimental research wearing of manufactured shoe samples, comparison, generalization and systematization of the results obtained. Results. The issue of foot anthropometry and problems of the human musculoskeletal system in dynamic and static positions was investigated. The issue of developing footwear for consumers with large feet and non-standard foot parameters was investigated. Manual measurement of the feet was carried out, processing, analysis and comparison with standardized values of the digital data array regarding the measurements of the lower extremities of the group of consumers who took part in the experiment were carried out. The technological and design procedure for building up individual parts of the insole, development of sketches, drawings, selection of materials, production of a shoe model in the material and the finished product according to a given technological sequence was determined. As a result of the work performed, an experimental trial wearing of the manufactured shoe samples by a group of consumers in the conditions of the environment and their professional activities was carried out according to the standardized methodology. Analysis of the results of organoleptic and laboratory studies confirms the high assessment of the quality and comfort of the developed shoe samples. Scientific novelty. For the first time, samples of large-sized anatomical shoes for household and special (professional) purposes were developed and manufactured. The demand for products in this segment was theoretically predicted by surveying respondents. Practical value. The results of this theoretical, analytical and experimental study, in particular the experimental wearing of shoe samples, contribute to the expansion of the information and parametric database based on the results of research, which can become the basis for revising the standards of compliance with the dimensional grid when creating unified insoles for the production of shoes. These studies have a positive practical result, so they are a promising direction for the development of the Ukrainian market of safe, environmentally friendly and competitive products of high quality and comfort.